Probing the surface of aqueous surfactant-perfume mixed solutions during perfume evaporation - Penfold, J; Thomas, R; Bradbury, R; Tucker, I; Petkov, J; Jones, C; Webster, J (Elsevier, 2017)
The rate of release or evaporation of perfume molecules from surfaces is a key factor in determining the impact of the perfume in a range of applications relating to home and personal care products. For mixtures of the anionic surfactant sodium dodecylsulfate and the model perfume linalool the rate of change of adsorption with time due to forced air flow over a fixed headspace was evaluated using neutron reflectivity over a period of up to ∼250 min. The measurements were made in the limit of the high flow rates where the evaporation is independent of the air flow rate. The amount of perfume at the interface decreases with time, and this occurs at a faster rate as the initial amount of perfume in solution is decreased. The variation of the perfume adsorption with time for different surfactant/perfume solution compositions illustrates the increasing importance of diffusion to the surface as the perfume concentration in solution decreases.